Intervention of Numbers Puzzle Against Short Memory Mental Retardated Children - Panzilion, Panzilion; Padila, Padila; Andri, Juli (JOSING: Journal of Nursing and Health, 2021)
The purpose of this study was to see the effect of number puzzle intervention on increasing short memory in children with mental retardation in SDLBN 05 Bengkulu City. This study uses a quantitative approach using a Quasy Experiment design, one group pre-post test with a nonequivalent control group design. This study uses a digit forward questionnaire by remembering the numbers from front to back, the digit forward numbers are 9 digits. The results of the univariate analysis of the intervention of 10 samples 7 (30%) with a less short memory and 3 (30%) short memory samples are good and after being given number puzzle therapy, it is known that out of 10 samples 8 (80%) have a good memory and 2 (20%) with the less category. The paired test results showed that there was an effect of puzzle therapy on increasing short memory in SDLBN 05 Bengkulu City with a p-value of 0,000. In conclusion, there is an effect of number puzzle therapy intervention on increasing short memory of children with mental retardation in SDLBN 05 Bengkulu City. Keywords: Number Puzzle, Mental retardation, Short memory